The Role of Internal Audit in Risk Management and Good Corporate Governance at PT. BPR Pijer Podi Kekelengen - Jonathan Pahothon Sianturi; Nisrul Irawati (Universitas KH. Abdul Chalim Mojokerto, 2024)
Internal audit is an important factor in implementing risk management and Good Corporate Governance. This research aims to find out how big the role of internal audit is in Risk Management and Good Corporate Governance (GCG). This research was conducted at PT. BPR Pijer Podi Kekelengen. The subjects of this research are the head of the internal audit division, audit staff, risk management staff, and compliance staff. This type of research is qualitative research with a descriptive approach which aims to provide a clear picture of the object under study based on primary data obtained through interviews and asking closed questions to the relevant officials. The results of the research conducted show the role of Internal Audit in Risk Management and Good Corporate Governance at PT. BPR Pijer Podi Kekelengen. Internal audit has carried out its duties well by carrying out comprehensive supervision of company parts following SOPs but still requires improvement in the quality and quantity of human resources. PT. BPR Pijer Podi Kekelengen has implemented GCG principles well in accordance with GCG principles.